The planning and implementation process of programmatic advertising campaigns in emerging markets. - Tiet, Thanh (2020)
Programmatic advertising has developed rapidly in recent years and become the driver of the exponential growth of online advertising. Programmatic advertising initially involved with programmatic buying and gradually evolved to include programmatic creative. While programmatic buying could be dated back from the 2000s and already developed, programmatic creative is a new phenomenon in recent years and still developing. In brief, programmatic advertising is the combination of technology and audience data, which allows brands to deliver personalised ads to the right target audience at scale. This thesis studies the situation of programmatic advertising and its planning and implementation process in emerging countries, especially Vietnam market. The study results suggest that programmatic advertising is leveraged for both long-term brand building campaigns and short-term direct response campaigns for different reasons. And each campaign objective has different planning and implementation process. In brief, the advertising process for short-term direct response campaigns is a non-linear process in which the planning phase and implementation phase are integrated with each other, while the advertising process for long-term brand building campaigns skews toward the linear spectrum and the two phases are clearly separated. Furthermore, the programmatic advertising process is data-driven because data are leveraged in all steps of the advertising process. Lastly, the advertising process requires a balanced combination between system automation and digital specialists’ involvement to be effective.